Respuesta :
(a) [tex]4.40\cdot 10^{20}N[/tex]
The distance between the Sun and the Earth is
[tex]d_{SE}=1.496 \cdot 10^11 m[/tex]
The distance between the Earth and the Moon is
[tex]d_{EM} = 3.84\cdot 10^8 m[/tex]
So, the distance between the Sun and the Moon, when the Moon is between the Earth and the Sun, is
[tex]d_SM = 1.496\cdot 10^{11}m -3.84\cdot 10^8 m=1.492\cdot 10^{11} m[/tex]
So the gravitational force between the Sun and the Moon is
[tex]F_{SM} = G \frac{M_S M_M}{d_{SM}^2}[/tex]
where
G is the gravitational constant
[tex]M_S = 1.988 \cdot 10^{30}kg[/tex] is the mass of the Sun
[tex]M_M = 7.384\cdot 10^{22}kg[/tex] is the mass of the Moon
[tex]d_{SM}=1.492\cdot 10^{11} m[/tex] is their distance
Substituting,
[tex]F_{SM} = (6.67\cdot 10^{-11}) \frac{(1.988\cdot 10^{30} kg)(7.384\cdot 10^{22}kg)}{(1.492\cdot 10^{11} m)^2}=4.40\cdot 10^{20}N[/tex]
(b) [tex]2.00\cdot 10^{20}N[/tex]
The gravitational force between the Earth and the Moon is
[tex]F_{EM} = G \frac{M_E M_M}{d_{EM}^2}[/tex]
where
G is the gravitational constant
[tex]M_E = 5.972 \cdot 10^{24}kg[/tex] is the mass of the Earth
[tex]M_M = 7.384\cdot 10^{22}kg[/tex] is the mass of the Moon
[tex]d_{EM}=3.84\cdot 10^{8} m[/tex] is their distance
Substituting,
[tex]F_{EM} = (6.67\cdot 10^{-11}) \frac{(5.972\cdot 10^{24} kg)(7.384\cdot 10^{22}kg)}{(3.84 \cdot 10^{8} m)^2}=2.00\cdot 10^{20}N[/tex]
(c) [tex]3.54\cdot 10^{22}N[/tex]
The gravitational force between the Earth and the Sun is
[tex]F_{ES} = G \frac{M_E M_S}{d_{ES}^2}[/tex]
where
G is the gravitational constant
[tex]M_E = 5.972 \cdot 10^{24}kg[/tex] is the mass of the Earth
[tex]M_S = 1.988 \cdot 10^{30}kg[/tex] is the mass of the Sun
[tex]d_{SE}=1.496 \cdot 10^{11} m[/tex] is their distance
Substituting,
[tex]F_{ES} = (6.67\cdot 10^{-11}) \frac{(5.972\cdot 10^{24} kg)(1.988\cdot 10^{30}kg)}{(1.496 \cdot 10^{11} m)^2}=3.54\cdot 10^{22}N[/tex]